Fundamentals of Business - Skripak, Stephen J.; Poff, Ron (Open textbook library., 2023)
Fundamentals of Business, 4th Edition is an open education resource intended to serve as a no-cost, faculty-customizable primary text for one-semester undergraduate introductory business courses. It covers the following topics in business: Teamwork; economics; ethics; entrepreneurship; business ownership, management, and leadership; organizational structures and operations management; human resources and motivating employees; managing in labor union contexts; marketing and pricing strategy; hospitality and tourism, accounting and finance, personal finances, and technology in business. The textbook was designed for use in Virginia Tech’s Pamplin College of Business introductory level business course, MGT1104 Foundations of Business and is shared under a Creative Commons Attribution Non-Commercial ShareAlike 4.0 license. If you are an instructor reviewing, adopting, or adapting this textbook, please help us understand your use by filling out this form http://bit.ly/business-interest. A testbank is now available by request for this book: http://hdl.handle.net/10919/93404. The testbank covers chapters 1-18 and (currently) aligns to previous editions of the textbook. It is available to any instructor who has adopted Fundamentals of Business in their course.